Plates, Plumes and Paradigms 2005
DOI: 10.1130/0-8137-2388-4.279
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary evidence for moderate mantle temperature anomalies associated with hotspot volcanism

Abstract: One of the characteristics of deep-rooted mantle plume models, and the hotspot volcanism with which they are associated is the presence of anomalously buoyant asthenosphere underlying the lithospheric plate. The presence of hot, upwelling, lowdensity asthenosphere causes shallowing of the seafloor over the plume center. It is commonly assumed that as the plume mantle disperses, greater subsidence occurs compared to normal oceanic crust. However, in this paper analysis of the sedimentary cover from a range of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…This does not explain, however, why the picrite cumulates that are often assumed to represent original melts, are common. The absence of plateau subsidence predicted by cooling models has been attributed to post-eruption magmatic underplating causing continuous crustal growth and bathymetric support [Clift, 2005] or to support from buoyant, depleted mantle residuum remaining after melt extraction, e.g., at the Ontong Java plateau [Robinson, 1988] and the Hawaiian swell [Phipps- Morgan et al, 1995]. On the other hand, the lack of such support in the North Atlantic has been explained by the suggestion that vigorous convection removed the residuum there.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This does not explain, however, why the picrite cumulates that are often assumed to represent original melts, are common. The absence of plateau subsidence predicted by cooling models has been attributed to post-eruption magmatic underplating causing continuous crustal growth and bathymetric support [Clift, 2005] or to support from buoyant, depleted mantle residuum remaining after melt extraction, e.g., at the Ontong Java plateau [Robinson, 1988] and the Hawaiian swell [Phipps- Morgan et al, 1995]. On the other hand, the lack of such support in the North Atlantic has been explained by the suggestion that vigorous convection removed the residuum there.…”
Section: Discussionmentioning
confidence: 99%
“…Bathymetry, and the history of sea-floor subsidence in the North Atlantic has been used to estimate asthenosphere temperature [Clift, 2005;Clift et al, 1998;Ribe et al, 1995]. The sea floor is anomalously shallow in the North Atlantic, and it has been suggested that this results from support by thermally buoyant plume-head material.…”
Section: The North Atlantic Igneous Provincementioning
confidence: 99%
See 2 more Smart Citations
“…They explained this by invoking late stage underplating and proposed that the formation of the Manihiki Plateau was related to a hotspot. The more recent analysis by Clift (2005) argues that the subsidence is less than typical for normal oceanic lithosphere, similar to that reconstructed for the Ontong-Java Plateau.…”
Section: Nassau P E N R H Y N B a S In C E N T R A L B A S I N O F T mentioning
confidence: 95%